2018
DOI: 10.1002/mrm.27434
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast 3D Bloch–Siegert B‐mapping using variational modeling

Abstract: Purpose Highly accelerated B ‐mapping based on the Bloch–Siegert shift to allow 3D acquisitions even within a brief period of a single breath‐hold. Theory and Methods The B dependent Bloch–Siegert phase shift is measured within a highly subsampled 3D‐volume and reconstructed using a two‐step variational approach, exploiting the different spatial distribution of morphology and B ‐field. By appropriate variable substitution the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Additionally, the numerical gradients were balanced after each GN‐step by calculating their L2‐norm and applying a scaling to match each other in the forward and adjoint evaluation of the gradient. In a subsequent preprocessing step, coil sensitivities were estimated from parameter‐averaged data using the method of Uecker et al Deviations from the nominal flip angle were taken into account by performing B1+ mapping with a modified Bloch‐Siegert and DREAM method for VFA respectively IRLL data. The Bloch‐Siegert map was acquired on a Cartesian grid with half the resolution of the VFA data and a block undersampling pattern with size of 12 × 4 as described by Lesch et al, leading to an acquisition time of about 15s for the whole 3D volume.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the numerical gradients were balanced after each GN‐step by calculating their L2‐norm and applying a scaling to match each other in the forward and adjoint evaluation of the gradient. In a subsequent preprocessing step, coil sensitivities were estimated from parameter‐averaged data using the method of Uecker et al Deviations from the nominal flip angle were taken into account by performing B1+ mapping with a modified Bloch‐Siegert and DREAM method for VFA respectively IRLL data. The Bloch‐Siegert map was acquired on a Cartesian grid with half the resolution of the VFA data and a block undersampling pattern with size of 12 × 4 as described by Lesch et al, leading to an acquisition time of about 15s for the whole 3D volume.…”
Section: Methodsmentioning
confidence: 99%
“…In a subsequent preprocessing step, coil sensitivities were estimated from parameter‐averaged data using the method of Uecker et al Deviations from the nominal flip angle were taken into account by performing B1+ mapping with a modified Bloch‐Siegert and DREAM method for VFA respectively IRLL data. The Bloch‐Siegert map was acquired on a Cartesian grid with half the resolution of the VFA data and a block undersampling pattern with size of 12 × 4 as described by Lesch et al, leading to an acquisition time of about 15s for the whole 3D volume. The resulting B1+ map is normalized to the nominal flip angle of the Bloch‐Siegert encoding pulse, leading to a spatially dependent correction factor for α.…”
Section: Methodsmentioning
confidence: 99%
“…The greater robustness of the interleaved acquisition scheme has led to its adoption in more recent work using this technique. 11,26 In the interleaved case, however, our numerical simulations showed that the phase never reached steady-state but rather a pseudo-steady-state that alternated between two conditions depending on the frequency of the preceding offresonance BS pulse. As a result, the difference in phase between interleaves is not solely due to the BSS effect and, therefore, does not match the phase difference of the sequential ordering scheme (Figure 2).…”
Section: Discussionmentioning
confidence: 80%
“…The resulting B1+ maps had visible artefacts and large biases (see Figure , right column). The greater robustness of the interleaved acquisition scheme has led to its adoption in more recent work using this technique …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation